Transcriptome Analysis of the Central Nervous System of Sea Slug (Onchidium reevesii) Exposed to Low-Frequency Noise - Tu, Zhihan; Tang, Liusiqiao; Zhang, Xiaoming; Jia, Jingjing; Shen, Heding (Frontiers in Marine Science, 2021)
Low-frequency noise has become a marine pollutant that cannot be ignored, but most studies have focused on the behavioral and physiological effects on marine vertebrates, with few studies in marine mollusks. Therefore, sea slug was used in this study to investigate the effect of low-frequency noise on its physiological aspects. This experiment was designed with different low-frequency noise (0, 100, 300, and 500 Hz) and different stimulation times (0, 6, and 12 h) to measure superoxide dismutase (SOD), malondialdehyde (MDA), and catalase (CAT) activities in hemolymph and transcriptomics in the control (C) and 6 and 12 h groups (L1 and L2) with 500 Hz noise. The results showed a positive correlation between antioxidant enzyme activity and low-frequency noise frequency (P < 0.05) and no correlation with time (P > 0.05). In central nervous system (CNS) transcriptomics, 2,460 and 3,268 genes had upregulated expression and 2,765 and 2,783 genes had downregulated expression in the L1 and L2 groups, respectively, compared to the C group. According to Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, low-frequency noise mainly affects signaling pathways such as cytokine-cytokine receptor interaction, the FoxO signaling pathway, natural killer cell-mediated cytotoxicity, apoptosis immune-related pathways, and energy metabolic pathways such as glycolysis, the TCA cycle, and glycerophospholipid metabolism, as well as neurological pathways such as GABAergic synapses, the synaptic vesicle cycle, amyotrophic lateral sclerosis (ALS) and other neurological pathways. This study would provide valuable reference information on the potential response of mollusks to low-frequency noise stress.